2006
DOI: 10.1002/pros.20426
|View full text |Cite
|
Sign up to set email alerts
|

Steroid sulfatase and estrogen sulfotransferase in human prostate cancer

Abstract: STS and EST are expressed and may be involved in local production and metabolism of estrogens in human prostate cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 19 publications
5
48
1
Order By: Relevance
“…It was reported that DHEAS is hydrolyzed by STS in LNCaP cells [27] and the expression of STS is increased in prostate cancer cells, compared to non-malignant prostate tissues, as determined by immunohistochemical staining [28]. In the present study, expression of STS mRNA was detected in LNCaP cells, and this expression was not affected under androgen-depleted conditions ( Figure 1C).…”
Section: Contribution Of Oatp1a2 To Dheas-induced Cell Growth In Lncasupporting
confidence: 63%
“…It was reported that DHEAS is hydrolyzed by STS in LNCaP cells [27] and the expression of STS is increased in prostate cancer cells, compared to non-malignant prostate tissues, as determined by immunohistochemical staining [28]. In the present study, expression of STS mRNA was detected in LNCaP cells, and this expression was not affected under androgen-depleted conditions ( Figure 1C).…”
Section: Contribution Of Oatp1a2 To Dheas-induced Cell Growth In Lncasupporting
confidence: 63%
“…These targets include tissues of the reproductive system, such as the mammary gland and uterus, cells in the hypothalamus and pituitary, bone, and liver, as well as the cardiovascular system, where estrogens exert cardioprotective effects [35]. In addition to stimulating normal mammary gland growth and duct development, pathological levels of estrogens increase proliferation and metastatic activity of breast cancer cells and stimulate proliferation of uterine cells [36,37]. While much is known about the physiology of estrogens, little has been documented about the oxidative regulation of SULTs.…”
Section: Discussionmentioning
confidence: 99%
“…Redox regulation of hSULT1E1 changes bioactive E 2 levels in vivo. This in turn is related to E 2 -dependent tumorigenesis in the breast, endometrium, and prostate [36,37]. Human liver cytosol (final concentration, 1.0 mg/ml) or purified hSULT1E1 (final concentration, 0.1 mg/ml) were incubated in Tris buffer (pH 6.2) at room temperature with various GSSG concentrations and durations, as indicated.…”
Section: Discussionmentioning
confidence: 99%
“…STS has been shown to be expressed in normal human prostate tissue (Reed et al 2005), prostate cancer cell lines LNCaP, DU-145 and PC3 (Nakamura et al 2006) and in primary prostate homogenates (Klein et al 1989). Furthermore, one study found that STS is expressed in the majority of localised prostate cancers showing higher expression in malignant tissues compared with benign (Nakamura et al 2006). The activity of STS has been proven within the human prostate for the desulphation of dehydroepiandrosterone sulphate (DHEAS) into DHEA, an androgen precursor (Farnsworth 1973).…”
Section: :6mentioning
confidence: 99%
“…The activity of STS has been proven within the human prostate for the desulphation of dehydroepiandrosterone sulphate (DHEAS) into DHEA, an androgen precursor (Farnsworth 1973). Moreover, E 1 synthesis from desulphation of E 1 S within the prostate is putatively 10-fold greater than synthesis via aromatase (Nakamura et al 2006). The relevance of STS in cancer has been more extensively studied in breast cancer, where there is significantly higher expression of STS than in normal breast (Utsumi et al 2000).…”
Section: :6mentioning
confidence: 99%